Effect of soaking time sodium metabisulfite (Na2S2O5) and carboxymethyl cellullose (CMC) on the characteristics of lowe banana starch - Said, Muhummad Ahmad; Chaniago, Ramadhani -; Prima, Muhammad Risky; Dawaso, Fatmawati - (Jurnal Agrotek Ummat, 2023)
Lowe's banana has the potential for high starch content. The processing of bananas into flour and starch offers more diverse development opportunities to achieve food security. The aim of this study was to determine the effect of soaking time in sodium metabisulphite and carboxy methyl cellulose solution on the chemical composition, starch content and gluten content of Lowe's banana flour. The design used was a completely randomised factorial design (CRD) with two factors: type of soaking agent (M) and soaking time (L). For each treatment, all contained 5 grams/litre of water with differences in the type of soaking agent, namely: water (M1), sodium metabisulphite (M2) and carboxymethyl cellulose (M3). As far as the soaking time is concerned, it consists of 3 treatments: (L1) = 6 hours; (L2) = 12 hours; and (L3) = 18 hours, so that there were 27 treatment units consisting of 3 x 3 different treatment combinations, which were then repeated three times. The research variables were proximate test, starch test and gluten test. The results showed that the longer the soaking time, the higher the water and protein content and the lower the ash, fat, carbohydrate, starch and gluten content. The best treatment was M1L3 which increased protein and decreased ash and gluten.